Pemberdayaan Masyarakat Kelambir Lima Kebun Melalui Pelatihan Kewirausahaan Berbasis Potensi Lokal - Indrawan, Muhammad Isa; Fatmawati, Irma; Rahayu, Sri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This community service program aims to improve the economic capacity of residents of Kelambir Lima Kebun Village through entrepreneurship training based on local potential. This area has various resources that have not been optimally utilized, such as agricultural products, traditional culinary arts, and household skills. However, limitations in entrepreneurial knowledge, business management, and market access are obstacles to the community's economic development. This activity was carried out in the form of training and mentoring that included identifying local potential, business planning, product innovation, simple financial management, and digital marketing strategies. The method used was participatory with an interactive training approach, group discussions, and hands-on practice. The results of the activity showed an increase in participants' understanding of the basic concepts of entrepreneurship and their ability to develop business ideas based on local resources. This service is expected to encourage the emergence of new entrepreneurs and increase the economic independence of the Kelambir Lima Kebun community in a sustainable manner.